Endovascular treatment of chronic cerebrospinal venous insufficiency in multiple sclerosis: a retrospective study. (6th March 2013) - Alroughani, R.; Lamdhade, S.; Thussu, A.
<x xml:space="preserve">Abstract</x> Background: Chronic cerebrospinal venous insufficiency (CCSVI) has been proposed to be associated with multiple sclerosis (MS). Zamboni et al. reported significant improvement in neurological outcomes in MS patients who underwent percutaneous transluminal angioplasty (PTA). Objectives: To retrospectively evaluate the neurological outcomes in MS patients who underwent PTA. Method: Relapsing remitting MS patients who underwent PTA and completed at least 1 year post-PTA were assessed. Patients with clinically isolated syndrome or progressive forms of MS were excluded. Primary endpoint was the proportion of relapse-free patients at 1 year. Secondary endpoints were change in mean Expanded Disability Status Scale (EDSS) score and proportion of patients with new magnetic resonance imaging (MRI) activity (defined as either gadolinium-enhancing or new T2 lesions) at 1 year. Results: Forty-five patients satisfied the inclusion criteria. Females constituted 71.1%. The mean age and mean disease duration were 33.76 and 7.16 years, respectively. At 1-year post-PTA, the proportion of relapse-free patients decreased from 84.44% to 66.67% (p = 0.085), whereas the mean EDSS score increased (p = 0.017). The proportion of patients with new MRI activity increased significantly from 17.78% to 44.44% (p = 0.012). A total of 35.6% of patients stopped their disease modifying therapies (DMTs). There was no difference among the patients who stopped their DMTs with respect to relapses, EDSS score or new MRI activity. Conclusion: The study revealed that PTA in relapsing remitting MS patients was not associated with any neurological improvement. However, there was an increase in disease activity irrespective of the adherence to DMTs. Further evidence of the association between CCSVI and MS is required.